Francis J. Moloney, A Body Broken for a Broken People: Divorce, Remarriage and the Eucharist (London: Darton, Longman and Todd 2015) - Crimella, Matteo (The Biblical Annals, 2016)
Book review: Francis J. Moloney, A Body Broken for a Broken People: Divorce, Remarriage and the Eucharist (London: Darton, Longman and Todd 2015). Pp. 303. £14,99. ISBN: 978-0-232-53204-3.